2024
DOI: 10.3847/1538-4357/ad1403
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Poynting Flux Vortices in the Solar Atmosphere and Their Role in Concentrating Energy

Suzana S. A. Silva,
Gary Verth,
Erico L. Rempel
et al.

Abstract: The nature of energy generation, transport, and effective dissipation responsible for maintaining a hot solar upper atmosphere is still elusive. The Poynting flux is a vital parameter for describing the direction and magnitude of the energy flow, which is mainly used in solar physics for estimating the upward energy generated by photospheric plasma motion. This study presents a pioneering 3D mapping of the magnetic energy transport within a numerically simulated solar atmosphere. By calculating the Finite Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…During the analyzed period, a magnetic tornado is generated by photospheric vortex flows, which is the same triggering mechanism as presented in many previous simulations (Kuniyoshi et al 2023;Silva et al 2024). The lifetime of the magnetic tornado is approximately   ( ) t 10 minutes 950 s 1550 s , corresponding to that of the photospheric vortex, which persists for about one granular turnover time.…”
Section: Simulation Overviewsupporting
confidence: 52%
See 1 more Smart Citation
“…During the analyzed period, a magnetic tornado is generated by photospheric vortex flows, which is the same triggering mechanism as presented in many previous simulations (Kuniyoshi et al 2023;Silva et al 2024). The lifetime of the magnetic tornado is approximately   ( ) t 10 minutes 950 s 1550 s , corresponding to that of the photospheric vortex, which persists for about one granular turnover time.…”
Section: Simulation Overviewsupporting
confidence: 52%
“…Magnetic tornadoes, identified as impulsive Alfvén waves originating from photospheric vortex motions within intergranular lanes (Wedemeyer-Böhm et al 2012;Battaglia et al 2021), display signatures observed in the photosphere or chromosphere, manifesting as swirling plasma motions (diameter ∼2 Mm; Shetye et al 2019;Dakanalis et al 2022). Magnetoconvection simulations focusing on the quiet Sun have indicated that magnetic tornadoes can contribute approximately 50% of the total Poynting flux into the corona (Kuniyoshi et al 2023;Silva et al 2024).…”
Section: Introductionmentioning
confidence: 99%